The Effect of Safety Shoe Insole Material on Subjects due to Prolonged Standing - Isa, Halim (2011)
Prolonged standing is common in working environment especially in manufacturing industries. Industrial workers exposed to prolonged standing when they spent more than 50% of their working hours standing. Most researchers found that prolonged standing will cause pain and discomfort in the back and lower limbs. Moreover, working under prolonged standing will make the industrial workers feel uncomfortable, pain and tired. In the long run, this will cause pain under the feet. Generally, industrial workers are provided with safety shoes however, most of the safety shoes are created for external safety purposes only. Hence, the objectives of this project are to identify the effectiveness of the safety shoe insole on industrial workers and provide better solutions to reduce pain under the feet among workers when exposed to prolonged standing. The effectiveness of the safety shoe insole has been assessed through experimental work conducted on ten subjects with weight ranging between 55 to 65kg and continuously standing for three hours using a foot pressure measurement device (foot pressure distribution). The subjects are provided with a safety shoe insole that is inserted in their shoes. The results for the foot pressure measurement showed that the average force under the feet for the right and left foot are 245.96N and 243.95N respectively with maximum force located under the heel area that led to the feel of discomfort and back pain. The combination of two materials (Polyurethane and Poron) used for the safety shoe insole have reduced the force under the feet to 159.6N.